2004
DOI: 10.1002/app.20001
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of silicone rubber with poly(ethylene glycol) hydrogel coatings

Abstract: Hydrogel coatings of monoacrylated poly-(ethylene glycol) (PEG) methyl ethers of different molecular weights were attached to silicon rubber surfaces and crosslinked with hexanediol diacrylate or ethoxylated trimethylolpropane diacrylate by UV polymerization. The wetting, evaluated with the water contact angles, correlated with the surface oxyethylene chain density, which was evaluated with the ESCA ϾCOOO/OCH 2 O ratio obtained from the C(1s) peak. As measured by the ESCA N(1s) peak, bovine serum albumin forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To overcome this problem, the external surfaces of the device were masked by covalent coupling of a poly(ethyleneglycol) derivative (PEGylation) in an effort to minimize the immune cell response 17. PEGylated silicon rubber has exhibited very low cell and platelet adhesion in vitro in comparison to blank silicone 23…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this problem, the external surfaces of the device were masked by covalent coupling of a poly(ethyleneglycol) derivative (PEGylation) in an effort to minimize the immune cell response 17. PEGylated silicon rubber has exhibited very low cell and platelet adhesion in vitro in comparison to blank silicone 23…”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the large amounts of serum present in cerebrospinal fluid (CSF),7 the cells and other living organisms such as bacteria that enter the brain during the insertion of catheter can colonize, proliferate and cause occlusion and/or infections 42. On the other hand, several studies have also reported protein/cell adhesion resistant properties by coating hydrophilic materials such as polyethylene glycol (PEG) on biomaterials 51, 52, 53. However, some reports have highlighted diminished PEG activity in the presence of protein aggregates49(which is the case in vivo) or during long-term use50 making PEGylation not ideal for the current application.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of the large amounts of serum present in cerebrospinal fluid (CSF), the cells and other living organisms such as bacteria that enter the brain during the insertion of the catheter can colonize, proliferate, and cause occlusion and/or infections . However, several studies have also reported protein/cell adhesion-resistant properties by coating hydrophilic materials such as polyethylene glycol (PEG) on biomaterials. However, some reports have highlighted diminished PEG activity in the presence of protein aggregates (which is the case in vivo) or during long-term use, making PEGylation not ideal for the current application. Similarly, few studies report protein-resistant agents called kosmotropes that create a barrier to proteins when present in solution. , However, to our knowledge, there are no reports showing tethered kosmotropic agents to biomaterials as a means to mitigate whole mammalian cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The two-step procedure enhances the EO content at the interface of about twice. Strong hydrophilic (water contact angle <10 • ) protein repellent surfaces (protein adsorption below 0.05 mg/m 2 ) could be prepared in this way on different polymers: PE, polyvinyl chloride, polystyrene, natural rubber, and polydimethyl siloxane [47][48][49][50][51][52]. R. Bischoff and G. Bischoff represent PEG hydrogel covering of polysiloxane tubing and tracheal prostheses preceded by plasma treatment [53].…”
Section: Bioinert Biomaterialsmentioning
confidence: 99%